Peran Guru dalam Mengembangkan Karakter Aswaja (Ahlussunnah Wal Jamaah) Melalui Pembelajaran Ke-NU-an - Diyah Prawestri; Nurhidayah Nurhidayah; Nadia Raifah Nawa Kartika (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to analyze the teacher's role in developing the Aswaja character in students atMI Giwangretno Sruweng and the obstacles experienced by the teacher in developing theAswaja character in students and the goals of developing the Aswaja character. This study usesa qualitative approach by examining the phenomenon as an observer in the development of theAswaja character in students. The researcher acts as an observer in the development of theAswaja character in students in class IV A MI Giwangretno Sruweng. The subjects of this studywere class teachers, religion teachers and students of class IV A MI Giwangretno. Datacollection techniques in this study used observation, interviews, documentation while dataanalysis techniques were data reduction, data presentation and then verification. The results ofthe research found by researchers that the teacher's role in developing the character of Aswajain students at MI Giwangretno is good. This can be seen from the students who are alwaysorderly in following the routine of reading Asmaul Husna every morning, praying dhuha incongregation, yasin every Friday, praying dhuhur in congregation, praying, pilgrimage, daringto call to prayer or iqomah in the home environment. Constraints experienced by teachersinclude: the lack of interest of students in participating in NU learning and limited time inlearning NU. Aswaja character development for students needs to be improved with habits thatare in accordance with NU culture about Aswaja. It is not only applied in madrasas, but canalso be applied by participants in everyday life and the community environment